Pyrexia of unknown origin and its aetiology in Pakistan. (October 2022) - Akhtar, Waheed; Awan, Sobia; Ishaq, Uzma; Malik, Asmara; Malik, Jahanzeb; Zaidi, Syed Muhammad Jawad
Pyrexia of unknown origin (PUO) and its aetiology vary considerably according to geography. We conducted a retrospective study to update our knowledge of PUO in Pakistan. PUO was defined as a febrile illness of >3 weeks' duration, a temperature of >38.3°C, and >3 outpatient visits or 3 days' hospitalization. Infection was the cause in 47.1%, malignancy in 23.1%, noninfectious inflammatory disease in 21.8%, miscellaneous causes in 1.2%, and in 6.8%, the cause of the fever was not found.